The health of rural Black communities during COVID: Some affirmations, some surprises - Sharlene D. Newman; Sharlene D. Newman; Kimberly Moss; Melonie Pichon; Deborah Scott; Kileema Rogers; Angela Orr; Chuong Bui; Pamela Payne-Foster; Pamela Payne-Foster (Frontiers in Public Health, 2023)
Background and objectiveThere are overwhelming health disparities in the Deep South. It is important to include the voice of communities affected by these disparities when developing interventions. The goal of the current study was to develop an academic community engaged partnership to strengthen the ability to address priority health concerns of rural African American communities with a focus on health literacy and health advocacy.MethodsA community-based participatory research approach was used to administer a 15-item community health survey in five rural communities led by African American mayors in Alabama (N = 752). The survey assessed the health concerns and the potential behaviors that may be associated with those health concerns.ResultsThe five communities demonstrated similarities as well as differences in both the health concerns endorsed and the potential health behaviors that may contribute to those concerns. All five communities identified cardiovascular disease as a health concern with three endorsing mental health issues and 2 dental health. With respect to behaviors, all five communities identified either unhealthy eating/exercise and substance use as concerns with one community identifying racism as a risky behavior affecting health.ConclusionThe results presented replicate CBPR studies demonstrating that communities are important sources of information about local health priorities and concerns.